Aula expandida en el espacio público - Ollivier Ortiz, Valeria (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
The COVID-19 pandemic created new paradigms about the way people worked and went to school. Millions of people had to adapt to them immediately, while most domestic spaces were not prepared for these changes. In countries like Mexico, where inequality and poverty are a common situation, the educational, economic and social gap increased. In Michoacán, 3 out of every 10 children have an educational lag, which is: they do not have mandatory basic education and do not attend to formal educational centers. This research project aims to generate alternative didactic scenarios in the city of Morelia, that help reduce the low academic performance, through the implementation of new education processes. This will be implemented by the intervention of public spaces through design, where local actions are carried out with collective learning programs. In order to mitigate the social and educational lag of the most disadvantaged by the pandemic, the intervention aims to produce a versatile, playful and replicable space to be implemented in public and semi-public spaces such as parks, squares, public buildings and schools.

La pandemia del COVID-19 generó nuevos paradigmas en la forma de trabajar y de asistir a la escuela. Millones de personas tuvieron que adaptarse a ellos de inmediato, mientras que la mayoría de los espacios domésticos no estaban preparados para estos cambios. En países como México, donde la desigualdad y la pobreza son una situación común, la brecha educativa, económica y social aumentó. En Michoacán 3 de cada 10 niños, presentan un rezago educativo, es decir no cuentan con la educación básica obligatoria y no asisten a centros educativos formales. El presente proyecto de investigación pretende generar escenarios alternativos a la educación en la ciudad de Morelia, que permitan disminuir el bajo rendimiento académico, a través de la implementación de nuevos procesos de enseñanza. Esto se llevará a cabo por medio de la intervención del diseño en el espacio público, donde se realicen acciones locales a través de programas de aprendizaje colectivo. Con el fin de mitigar las problemáticas sociales y educativas de los más desfavorecidos por la pandemia, la intervención busca generar un espacio versátil, lúdico y replicable para implementarse en espacios públicos y semipúblicos como parques, plazas, edificios públicos y escuelas.
Facultad de Arquitectura. Maestría en diseño avanzado
Keywords: info:eu-repo/classification/cti/4; FA-M-2022-1624; Artefacto urbano; Educación alternativa; Espacio público; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8561